Molecular and Clinical Characterization of CD80 Expression via Large-Scale Analysis in Breast Cancer - Zhang, Qin; Gao, Chaowei; Shao, Jianqiang; Zhang, Shengze; Wang, Peng; Wang, Zunyi (Frontiers in Pharmacology, 2022)
Cancer immunotherapy is emerging as a novel promising therapy option for cancer patients. Despite the critical role of CD80 in the regulation of immune responses, the expression and biological functions of CD80 in breast cancer remains unknown. In this study, we aim to investigate the role of CD80 both clinically and molecularly in breast cancer at a transcriptome level. Herein, we firstly analyzed the transcriptome profile and relevant clinical information derived from a total of 1090 breast cancer patients recorded in The Cancer Genome Atlas (TCGA) and then validated this in Molecular Taxonomy of Breast Cancer International Consortium (METABRIC) database (n=1904). We revealed the associations of CD80 and main molecular and clinical characteristics in breast cancer. Gene ontology analyses and Gene Set Variation Analysis (GSVA) of CD80-related genes revealed that CD80 were closely correlated with immune responses and inflammatory activities in breast cancer. Moreover, CD80 expression showed remarkable positive correlation with several infiltrated immune cell populations. In summary, CD80 expression was closely correlated with the malignancy of breast cancer and our findings suggest that CD80 might be a promising target for immunotherapeutic strategies. To the best of our knowledge, this is the first integrative study characterizing the role of CD80 expression in breast cancer via large-scale analyses.